Symbiotic stars in X-rays IV: XMM-Newton, swift and TESS observations - Lima, Isabel de Jesus (Astronomy and Astrophysics (A&A), 2024)
White dwarf symbiotic binaries are detected in X-rays with luminosities in the range of 1030 to 1034 ergs s−1 . Their X-ray emission arises either from the accretion disk boundary layer, from a region where the winds from both components collide or from nuclear burning on the white dwarf surface. In our continuous effort to identify X-ray emitting symbiotic stars, we studied four systems using observations from the Neil Gehrels Swift Observatory and XMM-Newton satellites in X-rays and from TESS in the optical. The X-ray spectra were fit with absorbed optically thin thermal plasma models, either single- or multitemperature with kT < 8 keV for all targets. Based on the characteristics of their X-ray spectra, we classified BD Cam as possible β-type, V1261 Ori and CD -27 8661 as δ-type, and confirmed NQ Gem as β/δ-type. The δ-type X-ray emission most likely arise in the boundary layer of the accretion disk, while in the case of BD Cam, its mostly-soft emission originates from shocks, possibly between the red giant and WD/disk winds. In general, we have found that the observed X-ray emission is powered by accretion at a low accretion rate of about 10−11 M⊙ yr−1 . The low ratio of X-ray to optical luminosities, however indicates that the accretion-disk boundary layer is mostly optically thick and tends to emit in the far or extreme UV. The detection of flickering in optical data provides evidence of the existence of an accretion disk.
Estrelas simbióticas em raios X IV: observações XMM-Newton, Swift e TESS
Keywords: stars; binaries; symbiotic - accretion; accretion disks - X-rays; individual; BD Cam; V1261 Ori; NQ Gem; CD -27 8661